Analisis Kemampuan Literasi Matematis Ditinjau dari Gaya Kognitif Siswa di MTs Al Mustaqim 1 - Fidela, Fidela; Asmah, Siti Nur; Nurdiana, Riyanti (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to describe students' mathematical literacy abilities in terms of cognitive style. This type of research is quantitative research with a descriptive approach. This research was carried out at Mts Al Mustaqim 1 Arang Limbung in class VIII C in the 2024/2025 academic year. Grouping students to see cognitive style uses a questionnaire instrument that has been filled in before continuing with test questions to see students' mathematical literacy abilities in terms of students' cognitive style.  The results of the research show that based on the average score obtained by students with the Field Dependent cognitive style, there were 12 people with an average score of 44.61, which is included in the low criteria, and students with the Field Independent cognitive style were 4 people with an average score of 48. .06 is included in the low criteria. Based on the problem-solving process and achievement of FI students' mathematical literacy ability indicators, it is better than FD students, as evidenced by FI fulfilling 2 indicators well while FD students only fulfill 1 indicator.